MAPPING STUDENT LEVELS USING THE COMMON EUROPEAN FRAMEWORK OF REFERENCE FOR LANGUAGES (CEFR) AS A FIRST STEP IN DEVELOPING ENGLISH LANGUAGE MATERIALS - Fitra Elia (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
English language instructors regularly encounter difficulties teaching ESP (English for Specific Purposes) classes in higher education since they must instruct students with various skill levels. Lecturers in this topic are needed to produce appropriate and targeted teaching materials adapted to the students' study program backgrounds. In addition to variations in majors, unclear proficiency level requirements frequently result in materials that are out of step with students' actual aptitudes. The aim of this article is to describe how the Common European Framework of Reference for Languages (CEFR) is used to map student competency levels in order to create ESP materials. In order to determine skill level mapping in creating materials, this study used a descriptive-reflective methodology that involved classroom observations, documentation of CEFR test results, and teaching practice. The results show that CEFR-based level mapping helps instructors create learning objectives, choose text kinds, and create instructional materials that are suitable for students' skill levels. Material development becomes more targeted, practical, and efficient with well-defined level criteria. As a level mapping tool, the CEFR is essential to raising the standard of ESP learning creation and implementation in higher education.